Synthesis and Characterization of Polyphosphazenes Modified with Hydroxyethyl Methacrylate and Lactic Acid - Evelyn Carolina Martínez Ceballos; Ricardo Vera Graziano; Gonzalo Martínez Barrera; Oscar Olea Mejía (International Journal of Polymer Science)
Poly(dichlorophosphazene) was prepared by melt ring-opening polymerization of the hexachlorocyclotriphosphazene. Poly[bis(2-hydroxyethyl-methacrylate)-phosphazene] and poly[(2-hydroxyethyl-methacrylate)-graft-poly(lactic-acid)-phosphazene] were obtained by nucleophilic condensation reactions at different concentrations of the substituents. The properties of the synthesized copolymers were assessed by FTIR, 1H-NMR and 31P-NMR, thermal analysis (DSC-TGA), and electron microscopy (SEM). The copolymers have a block structure and show two Tg's below room temperature. They are stable up to a temperature of 100°C. The type of the substituents attached to the PZ backbone determines the morphology of the polymers.